Reproductive isolation by different time of drone flight between Apis cerana (Fabricius, 1793) and Apis vechti (Maa, 1953) - Koeniger, N.; Koeniger, G.; Tingek, S.; Mardan, M.; Rinderer, T. E. (1988)
In Sri Lanka the three honeybee species Apis florea, Apis cerana and Apis dorsata are found in the same biotope. The daily periods of drone flight were found to be specific O( ENIKGER and AW-YALGUN1ASE K,ERA 1976). According to NT RUETR (1988) this behavioral isolation is a more complete separation than the reproductive barrier between A. mellifera and A. cerana. The three honeybees, A. cerana, A. vechti and A. dorsata are naturally distributed in the same habitat. We compared the time of drone flight between these honeybees in Sabah (North East Borneo).